MI-5. Volume 03 [videorecording (DVD)] - Bailey, Rob; Macfadyen, Matthew, 1974-; Hawes, Keeley, 1976-; Firth, Peter, 1953- (BBC Video ; Distributed by Warner Home Video, 2005)
Worlds collide and nothing is what it seems in the thrilling new installment of MI-5. While Tom has been branded a traitor, and Harry is in the hospital, an enigmatic agent, Adam Carter, has been recruited from MI-6 to help pick up the broken pieces.